2019
DOI: 10.1021/acsmacrolett.9b00783
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Nanoparticles as Initiators for Radical Polymerization of Vinyl Monomers

Abstract: Sonication of gallium or gallium-based liquid metals in an aqueous solution of vinyl monomers leads to rapid free radical polymerization (FRP), without the need for conventional molecular initiators. Under ambient conditions, a passivating native oxide separates these metals from solution and renders the metal effectively inert. However, sonication generates liquid metal nanoparticles (LMNPs) of ∼100 nm diameter and thereby increases the surface area of the metal. The exposed metal initiates polymerization, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 52 publications
3
133
2
Order By: Relevance
“…Lastly, there has been increasing interest in utilizing LM nanodroplets for injection in blood for imaging 33 or near-infrared photothermal tumor ablation 34 as well as for nanoparticular mediated polymerization. 35,36 Although not directly related to LM nanocomposites, these applications demonstrate the extraordinary versatility of liquid metal nanoparticles and their potential for wide impact in elds ranging from polymer engineering to nanomedicine.…”
Section: Lm Nanodroplet Synthesismentioning
confidence: 99%
“…Lastly, there has been increasing interest in utilizing LM nanodroplets for injection in blood for imaging 33 or near-infrared photothermal tumor ablation 34 as well as for nanoparticular mediated polymerization. 35,36 Although not directly related to LM nanocomposites, these applications demonstrate the extraordinary versatility of liquid metal nanoparticles and their potential for wide impact in elds ranging from polymer engineering to nanomedicine.…”
Section: Lm Nanodroplet Synthesismentioning
confidence: 99%
“…Without the presence of any additional initiator, in situ free radical polymerization was also initiated by sonicating EGaIn in the aqueous solution of vinyl monomers. [ 19 ] The resultant macromolecular shells, when being negatively charged (e.g., alginate [ 3a ] ), could further be reinforced by cross‐linking into the microgels via Ga 3+ produced from EGaIn oxidization. In contrast to the ultrathin shells of oxides and amphiphiles, these flexible macromolecular shells had the thickness tuned from several to dozens of nanometers, [ 3,14,17,20 ] offering both the efficient protection barrier and additional functionalities for multiple applications of EGaIn droplets.…”
Section: Figurementioning
confidence: 99%
“…In contrast to molecular adsorption of small amphiphiles, [ 3b,11a ] in situ polymerization offered a promising opportunity to produce endurable shells of EGaIn capsules from monomers. [ 18 ] Besides the recently reported free radical polymerization of vinyl monomers, [ 19 ] ring‐opening polymerization would enable to synthesize more diverse polymeric shells of EGaIn capsules, for example, biodegradable and biocompatible polylactones, [ 22 ] which could offer not only potential applications in the biomedical field, [ 22a ] but also the compatibility with many different polymers. The polylactone shells were synthesized by following a facile “one‐batch” procedure, for example, sonicating bulk EGaIn in fluidic ε‐CL under N 2 atmosphere and then maintaining at 140 °C for polymerization ( Figure A).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…12 Recent work has shown that Ga based liquid metals can also be used as a solvent for the synthesis of a wide range of nanomaterials via chemical reactions that occur at the surface of the liquid metal under a variety of conditions including galvanic exchange at the surface of large liquid metal droplets or under sonication conditions which leads to composites containing gold that are catalytically active, 13 metal oxides such as MnO 2 that have photocatalytic properties, 14 Prussian blue nanomaterials, 15 as well as the ability to polymerise materials around the surface of liquid metal droplets. [16][17][18] One aspect that always needs to be considered when using galinstan, EGaIn or Ga in the liquid form is that when these materials are exposed to an oxygen containing atmosphere they spontaneously form a self limiting $0.7 nm layer of Ga 2 O 3 around the outside of the droplet, even when containing additional In or Sn components. 19 This phenomenon can be explained by calculation of the Gibbs free energy of formation (DG f ) of gallium oxide which is much lower than In 2 O 3 or SnO 2 which therefore results in preferential formation of Ga 2 O 3 at the surface.…”
Section: Introductionmentioning
confidence: 99%